P21 Hypoxia-induced Neutrophil Survival Is Dependent On Phosphoinositide 3-kinase (pi3-k)-mediated Signalling. (10th November 2014) - Palazzo, S; Porter, L; Juss, JK; Hessel, E; Amour, A; House, D; Begg, M; Chilvers, ER
Abstract : Introduction and objectives: Neutrophils (PMNs) are a key component of the innate immune response to invading pathogens. They accumulate at sites of inflammation and infection, which are typically characterised by low oxygen tensions (e.g. in the acute respiratory distress syndrome (ARDS)). Human PMNs undergo constitutive apoptosis, their survival contingent upon pro-survival and pro-apoptotic signals derived from their microenvironment. Hypoxia profoundly delays PMN apoptosis, resulting in persistence of PMNs at inflammatory foci and this may perpetuate hypoxia-mediated lung injury. Given the importance of phosphoinositide 3-kinase (PI3-K) signalling in cytokine-mediated neutrophil survival, we hypothesised that hypoxia-induced PMN survival may also involve PI3-K-mediated signalling. Methods: Highly pure PMNs isolated from healthy volunteers were incubated for 20 h under normoxic (20 kPa) and physiologically relevant hypoxic (3 kPa) conditions with a pan-PI3-K inhibitor (LY294002 at 10 μM), a novel pan-Class I PI3-K inhibitor (ZSTK474 at 1 μM, 3 μM and 10 μM) or novel PI3-K Class I isoform-selective inhibitors (PI3-Kδ at 1 μM; PI3-Kγ at 3 μM and 10 μM, or PI3-Kδγ at 3 μM). PMNs were also incubated in normoxia and hypoxia in the presence of GM-CSF (1 ng/ml) with the same panel of inhibitors, allowing comparison with GM-CSF mediated survival, which is largely PI3-K dependent. PMN apoptosis was assessed using two complementary techniques – morphology and flow cytometry following annexin V-FITC and propidium iodide staining. Results: Compared with normoxia, hypoxia promoted PMN survival (mean% ± SEM apoptotic cells at 20 h; 30.9 ± 1.9 vs. 59.0 ± 1.8 respectively, p < 0.0001). Both pan-PI3-K inhibitors reversed the pro-survival effect of hypoxia in a concentration-dependent manner, LY294002 (10 μM; 60.3 ± 4.0, p < 0.0001) and ZSTK474 (10 μM; 58.3 ± 2.6, p < 0.0001) without affecting the basal rate of apoptosis. This effect was not seen with the dual PI3-Kδγ inhibitor (3 μM; 43.8 ± 7.6) or individual PI3-Kδ (1 μM; 43.0 ± 5.8) and γ inhibitors (3 μM; 34.9 ± 4.5 and 10 μM; 32.6 ± 3.6). Conclusions: Our results indicate that hypoxia-induced PMN survival is PI3-K dependent. Targeting this pathway may accelerate PMN apoptosis, resulting in resolution of inflammation.